Improvement of Nemadectin Production by Overexpressing the Regulatory Gene nemR and Nemadectin Biosynthetic Gene Cluster in Streptomyces Cyaneogriseus - Wu, Yuan-Jie; Yang, Song-Bai; Zhang, Zheng-Yu; Chen, Shao-Xin (Pharmaceutical Fronts, 2020)
Nemadectin, a 16-member macrocyclic lactone antiparasitic antibiotic, is produced by Streptomyces cyaneogriseus subspecies noncyanogenus. Moxidectin, a C-23 oximate derivative of nemadectin, is widely used as a pesticide due to its broad-spectrum, highly efficient, and safe anthelmintic activity. NemR, a LAL family regulator, is encoded by nemR and is involved in nemadectin biosynthesis in S. cyaneogriseus. In this report, gene disruption and complementation experiments showed that nemR plays a positive role in the biosynthesis of nemadectin. The transcription level of nemadectin biosynthetic genes in the nemR knockout strain was significantly decreased compared with those in the wild-type strain MOX-101. However, overexpression of nemR under the control of native or strong constitutive promoters resulted in the opposite, increasing the production of nemadectin by 56.5 or 73.5%, respectively, when compared with MOX-101. In addition, the gene cluster of nemadectin biosynthesis was further cloned and overexpressed using a CRISPR method, which significantly increase nemadectin yield by 108.6% (509 mg/L) when compared with MOX-101.
Keywords: nemadectin; overexpression; biosynthesis gene cluster; Streptomyces cyaneogriseus